The Effect of Spiritual Intelligence and Religious Faith on Self-Regulation - Lufiana Harnany Utami; Sandi Marahhul Mingtio; Abdul Muhid (Universitas Muhammadiyah Yogyakarta, 2022)
Most Muslims find it hard to memorize the Qur’an due to certain factors. This research explored the effect of spiritual intelligence and religious faith on self-regulation. Having quantitative design, three instruments were used in this analysis; self-regulation scale (S-SR) (α=0.621), religious faith scale (S-RF) (α=0.986), and spiritual intelligence scale (S-SI) (α=0.890). Four hundred (400) students in the tahfiz Al-Qur’an program from some Islamic boarding schools in Surabaya were selected through purposive sampling. The results from multiple regression showed that spiritual intelligence and religious faith significantly predicted self-regulation. In other words, both spiritual intelligence and religious faith had a positive effect on self-regulation. Besides, spiritual intelligence also positively affected self-regulation. The more positive students assessed their spiritual intelligence, the higher their self-regulation. That self-regulation then made students get more engaged with their activity of memorizing the Quran.